Internal workload and non-contact injury: a one-season study of five teams from the UEFA Elite Club Injury Study - McCall, A.; Dupont, G.; Ekstrand, J. (British Journal of Sports Medicine, 2018)
Background Internal workload (ie, from training and matches) is considered one of the most important injury risk factors for elite European football teams, however there is little published evidence to support this belief.